2012
DOI: 10.1111/j.1095-8312.2012.01961.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic spleen mass in wild and domestic American mink

Abstract: The immune system is considered to be an energetically expensive component of an individual's life history. Investment in the immune system can depend on the environment that an individual finds itself in. The American mink, Neovison vison, exists in the natural environment and on fur farms. The natural environment and mink farm differ in many ways, such as wild mink being exposed to many parasites that are less prevalent and less abundant in the domestic environment because of veterinary care. We collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
4
1
Order By: Relevance
“…A difference in relative spleen weight between the sexes was found in this study. This has been reported earlier [ 37 ] and the reason for the difference is not clear. In the male mink in this study, the relative spleen weight was associated with being AMDV positive and having AMDV antibodies, but not in the female mink (possibly due to a smaller sample size).…”
Section: Discussioncontrasting
confidence: 46%
“…A difference in relative spleen weight between the sexes was found in this study. This has been reported earlier [ 37 ] and the reason for the difference is not clear. In the male mink in this study, the relative spleen weight was associated with being AMDV positive and having AMDV antibodies, but not in the female mink (possibly due to a smaller sample size).…”
Section: Discussioncontrasting
confidence: 46%
“…Studies through time at a Northern Territory site showed higher rates of food intake and larger fat bodies in toads at the invasion front compared to the same site a few years later when density was higher (Brown et al ., ). The observed shift in spleen size could result either from a positive association with body condition or a negative association with parasite exposure (Vicente, Pérez‐Rodríguez & Gortazar, ; Schulte‐Hostedde, Bowman & Nituch, ). Although relative spleen size is often used as a gross measure of immunocompetence (Morand & Poulin, ; Corbin et al ., ; Koprivnikar & Leung, ), the causes and effects of mass variation are difficult to disentangle in an organ with such a multitude of functions (Smith & Hunt, ; Vicente et al ., ; Koprivnikar & Leung, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, regardless of the infection females had higher spleen weight to body weight ratio than males. The difference of relative spleen weight between sexes has been reported elsewhere ( Schulte-Hostedde, Bowman & Nituch, 2012 ; Persson et al, 2015 ), but the reason for sexual disparity remains unclear. Moore & Wilson (2002) suggested a shift of energy resources towards reproduction and/or growth over the immune system in male mammals and immunosuppressive side effects of androgenic hormones.…”
Section: Discussionmentioning
confidence: 88%
“…The size of immune organs ( i.e., spleen, performing important immune functions) has been commonly used to describe animals’ investment in immunological response to various factors ( John, 1994 ; Schulte-Hostedde, Bowman & Nituch, 2012 ). In the study AMDV infected mink had significantly higher spleen weight to body weight ratio.…”
Section: Discussionmentioning
confidence: 99%